Aeromonas hydrophila ST251 and Aeromonas dhakensis are major emerging pathogens of striped catfish in Vietnam - Bartie, Kerry L.; Ngô, Thao P. H.; Bekaert, Michaël; Hoang Oanh, Dang Thi; Hoare, Rowena; Adams, Alexandra; Desbois, Andrew P. (Frontiers in Microbiology, 2023)
Aeromonads are ubiquitous in aquatic environments and several species are opportunistic pathogens of fish. Disease losses caused by motile Aeromonas species, particularly Aeromonas hydrophila, can be challenging in intensive aquaculture, such as at striped catfish (Pangasianodon hypophthalmus) farms in Vietnam. Outbreaks require antibiotic treatments, but their application is undesirable due to risks posed by resistance. Vaccines are an attractive prophylactic and they must protect against the prevalent strains responsible for ongoing outbreaks. This present study aimed to characterise A. hydrophila strains associated with mortalities in striped catfish culture in the Mekong Delta by a polyphasic genotyping approach, with a view to developing more effective vaccines. During 2013-2019, 345 presumptive Aeromonas spp. isolates were collected at farms in eight provinces. Repetitive element sequence-based PCR, multi-locus sequence typing and whole-genome sequencing revealed most of the suspected 202 A. hydrophila isolates to belong to ST656 (n=151), which corresponds to the closely-related species Aeromonas dhakensis, with a lesser proportion belonging to ST251 (n=51), a hypervirulent lineage (vAh) of A. hydrophila already causing concern in global aquaculture. A. dhakensis ST656 and vAh ST251 isolates from outbreaks possessed unique gene sets compared to published A. dhakensis ST656 and vAh ST251 genomes, including antibiotic-resistance genes. The sharing of resistance determinants to sulphonamides (sul1) and trimethoprim (dfrA1) suggests similar selection pressures acting on A. dhakensis ST656 and vAh ST251 lineages. The earliest isolate (from 2013) lacked most resistance genes, suggesting relatively recent acquisition and selection, and this underscores the need to reduce antibiotics use where possible to prolong their effectiveness. A novel PCR assay was designed and validated to distinguish A. dhakensis ST656 and vAh ST251 strains. This present study highlights for the first time A. dhakensis, a zoonotic species that can cause fatal human infection, to be an emerging pathogen in aquaculture in Vietnam, with widespread distribution in recent outbreaks of motile Aeromonas septicaemia in striped catfish. It also confirms vAh ST251 to have been present in the Mekong Delta since at least 2013. Appropriate isolates of A. dhakensis and vAh should be included in vaccines to prevent outbreaks and reduce the threat posed by antibiotic resistance.